Chemical, functional and pasting properties of starches and flours from new yam compared to local varieties - Effah-Manu, L.; Wireko-Manu, F.D.; Agbenorhevi, J.K.; Maziya-Dixon, Busie; Oduro, I. (Informa UK Limited, 2022)
The potential uses of starches and flours depend on their physicochemical and functional properties. The chemical composition, functional and pasting properties of starch and flours obtained from some newly developed yam varieties from the Crops Research Institute (CRI), Ghana were evaluated, and compared with the existing local varieties. The results showed that the physicochemical and functional properties varied among the varieties studied. The CRI varieties were grouped in a principal component analysis as moisture (afase pa), amylose content (ahodenfo, soanyinto, afase biri), high starch content, bulk density and water absorption capacity (kukrupa, Mankrong pona, CRI pona). Starch pasting characteristics showed that Mankrong pona, CRI pona and afase pa exhibited stable pastes whereas afase biri, Mankrong pona and, afase soanyinto could be utilized for high-temperature processing. Overall, the new CRI varieties showed considerable functionalities that could be explored for potential food and industrial applications as compared to the existing local varieties.